The effect of KOH concentration and calcination temperature on the cement clinker catalyst activity in the transesterification of off-grade palm oil into biodiesel. Issue 1 (February 2021) - Helwani, Z; Negara, W S; Zahrina, I; Amraini, S Z; Idroes, G M; Muslem; Idroes, R
Abstract: Cement clinker has been researched and has shown good performance as a heterogeneous catalyst in the biodiesel production process. The purpose of this study was to synthesize and characterize a cement clinker/KOH catalyst, to determine the effect of KOH concentration and calcination temperature on biodiesel yield. The catalysts were prepared by impregnation-calcination in the various KOH concentrations of 5, 10 and 15% and the calcination temperature of 500, 600 and 700 °C. The transesterification process was carried out for 3 hours with a mole ratio of oil: methanol of 4:1, reaction temperature of 65 °C, catalyst concentration of 6% wt oil, and stirring of 400 rpm. The results showed that the catalyst with the KOH concentration of 15% and the calcination temperature of 700 °C had the best performance with a biodiesel yield of 88.82%. The catalyst has a surface area of 9.622 m 2 /g, basicity of H_> 12.2 and a crystalline phase of 3CaO.SiO2, K2 CO3, Ca(OH)2, and K2 O. From the research, it is known that calcination temperature and KOH concentration in the impregnation process are directly proportional to the biodiesel yield.